2012
DOI: 10.1021/jp300514f
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Cyclotrimerization Kinetics of C2H2 at a Cu(110) Surface

Abstract: The kinetics of acetylene adsorption and cyclotrimerization was studied by vibrational sum-frequency generation spectroscopy (SFG) and density functional theory (DFT) calculations. At low temperature, SFG shows two resonances corresponding to acetylene adsorbed in two different sites. Upon heating, two new vibrational resonances appear. We interpret these resonances as being due to C 2 H 2 island formation and adsorbed C 4 H 4 , which is the intermediate in the subsequent cyclotrimerization reaction to form be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 61 publications
3
22
0
Order By: Relevance
“…Such a possibility has been demonstrated in a surface assisted cyclo‐dehydrogenation experiment . Consistently, it was found that benzene can be formed by cyclotrimerization of C 2 H 2 on Cu(110) surface, which is an exothermic reaction with a moderate activation barrier of 0.79 eV . It is thus reasonable to assume that dehydrogenation is a reaction involved during most of or even the whole graphene growth process.…”
Section: Graphene Growth On a Cu Substratementioning
confidence: 61%
See 1 more Smart Citation
“…Such a possibility has been demonstrated in a surface assisted cyclo‐dehydrogenation experiment . Consistently, it was found that benzene can be formed by cyclotrimerization of C 2 H 2 on Cu(110) surface, which is an exothermic reaction with a moderate activation barrier of 0.79 eV . It is thus reasonable to assume that dehydrogenation is a reaction involved during most of or even the whole graphene growth process.…”
Section: Graphene Growth On a Cu Substratementioning
confidence: 61%
“…moderate activation barrier of 0.79 eV. [ 45 ] It is thus reasonable to assume that dehydrogenation is a reaction involved during most of or even the whole graphene growth process.…”
Section: Dehydrogenation Of Hydrocarbonmentioning
confidence: 99%
“…Moreover, carbon dimers containing hydrogen are very unfavorable on a surface with low adsorption energies, even in defects, and desorb or immediately decompose even at very low temperatures, as demonstrated in temperature‐programmed desorption (TPD) and thermal desorption spectroscopy (TDS) experiments . Complementary studies of acetylene (CH≡CH) aromatization over transition metals also demonstrated that the benzene ring is not stable at the metallic surface . Therefore, in the case of Cu, Reaction D with z = 0 should be considered in carbon deposition, this moment being the most probable to complete the dehydrogenation and the formation of CC bonds with sp 2 ‐hybridization.…”
Section: Cvd Synthesis and Growth Of Graphenementioning
confidence: 99%
“…This linear increase in adsorption energy with the chain length has been interpreted in terms of bonding configurations in which the alkane chains lie parallel to the metal surface [2,[20][21][22][23]. For unsaturated hydrocarbons such as ethylene and acetylene, their adsorption on metal surfaces in general can be described within the Dewar-Chatt-Duncanson chemisorption model, in which the bonding is formed via a π-donation from the adsorbate into empty metal-states coupled with back-donation from the metal into the empty orbital of the hydrocarbon [24][25][26][27][28]. This bonding configuration entails a rehybridization of the carbon atoms, which results in a C-C bond elongation and an upward "bending" of the hydrogen atoms from the surface [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%